2014
DOI: 10.1051/fruits/2014006
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient and mineral assessment of edible wild fig and mulberry fruits

Abstract: Nutrient and mineral assessment of edible wild fig and mulberry fruits.Abstract -Introduction. Edible wild plants are nature's gift to mankind. Considering the growing need to identify alternative bio-nutritional sources, some underutilized species of figs (Ficus carica L., F. palmata Forssk., F. racemosa L.) and mulberries (Morus alba L., M. nigra L, M. laevigata Wall.) of the family Moraceae were evaluated as wild edible fruits to study their nutritive and mineral composition in order to prioritize their edi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 23 publications
3
34
1
Order By: Relevance
“…Wild food plants have become very important for the food industry as they can be used to replace synthetic chemicals and nutraceuticals (Sadia et al, 2014); however, the nutritional, economic, and sociocultural potential of neglected and underutilized natural food resources have yet to be fully exploited and are suffering from a lack of research interest (Beccaro et al, 2015;Donno et al, 2014). For example, data on the antioxidant properties of several plant resources, in particular plants not used in nutrition and medicine, are still lacking.…”
Section: Fresh Fruit and Derived Products: New Sources For Health-promentioning
confidence: 99%
“…Wild food plants have become very important for the food industry as they can be used to replace synthetic chemicals and nutraceuticals (Sadia et al, 2014); however, the nutritional, economic, and sociocultural potential of neglected and underutilized natural food resources have yet to be fully exploited and are suffering from a lack of research interest (Beccaro et al, 2015;Donno et al, 2014). For example, data on the antioxidant properties of several plant resources, in particular plants not used in nutrition and medicine, are still lacking.…”
Section: Fresh Fruit and Derived Products: New Sources For Health-promentioning
confidence: 99%
“…In recent years, wild food plants have become very attractive to the food industry, prompting their use as replacements for synthetic chemicals and nutraceuticals (Donno, Beccaro, Mellano, Cerutti, & Bounous, 2013b;Sadia et al, 2014), but neglected and underutilized natural food resources are suffering from less attention and research, and their nutritional, economic and socio-cultural potentials are not fully exploited (Beccaro et al, 2014;Donno, Beccaro, Mellano, Cerutti & Bounous, 2014b, 2014c: data on antioxidant properties of several plants, particularly those that are not used in nutrition and medicine, still lack (Sadia et al, 2014). Therefore, investigation of such properties has been of interest mainly for finding new sources for natural antioxidants, functional foods and nutraceuticals: several researches investigated the nutraceutical properties of Morus spp.…”
mentioning
confidence: 99%
“…Three studies were included in this review to evaluate the mineral contents of Ficus carica that is crucial for bone health (Khan et al 2011;Sadia et al 2014;Soni et al 2014). Khan et al (2011) was the earliest to conduct physicochemical profiling of Ficus carica (Sadia et al 2014).…”
Section: Evaluation Of Major Mineral Contents Of Ficus Carica Crucialmentioning
confidence: 99%
“…Three studies were included in this review to evaluate the mineral contents of Ficus carica that is crucial for bone health (Khan et al 2011;Sadia et al 2014;Soni et al 2014). Khan et al (2011) was the earliest to conduct physicochemical profiling of Ficus carica (Sadia et al 2014). Their findings showed that their fig samples contain high amount of potassium (K) at 382.4-611.5 mg/100 g. This is followed by magnesium (Mg) at 110.50-202.40 mg/100 g, Calcium (Ca) 78.72-132.80 mg/100 g and phosphorous (P) at 31.91-76.96 mg/100 g (Khan et al 2011).…”
Section: Evaluation Of Major Mineral Contents Of Ficus Carica Crucialmentioning
confidence: 99%
See 1 more Smart Citation